Aestheticized temples, rationalized affects: sacred modernities and the micro-regulation of Hinduism in Singapore - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2022)
This paper develops the idea of “sacred modernities” to explore how the state- led regulation of religion shapes religious communities and religious subjects therein. Sacred modernities define the ways in which sacredness is understood and engaged with under conditions of secular modernity, and in particular, how sacredness is experienced within a context of micro-regulated religious space. We illustrate these ideas through an empirical examination of how Singapore’s Hindu community engages with the idea of sacredness in and through the temple. By contrasting the experiences of Singaporean and non-Singaporean Hindus, we argue that Singapore’s temples offer an aestheticized experience of the sacred that is rational in its affects. Differential expectations and experiences of the sacred can reveal divisions within the Hindu community along Singaporean/migrant lines.